Letter (copy) : Help for the Workers of Spain Fund - Tewson, Vincent
028-0190-001 HVT/FC/EK/2. Secretary's. 15th September, 1936. Mr. D. Dubinsky, The International Ladies Garment Workers' Union, 3, West 16th Street, New York, America. Dear Mr. Dubinsky, HELP FOR THE WORKERS OF SPAIN FUND. I am enclosing receipt for a further draft of £1,986.2.0. and would like to convey to you our thanks for the splendid support which is being rendered by our colleagues in the United States of America. Sir Walter is now on his way to America and no doubt you will be seeing him the course of the next week or ten days. Yours sincerely, Assistant Secretary. Receipt. 292/946/28/190